Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa MAN 1 Lombok Timur - Wahyuni, Sri Hida (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to improve student learning outcomes and activeness through the application of discovery learning models. This research method uses classroom action research which consists of 2 cycles. Each cycle consists of 4 (four) stages, namely planning, implementing, observing and reflecting. The subjects of this study were students of class XII MIA-1 MAN 1 East Lombok. The research instrument used observation sheets, documentation, and tests. The data analysis technique of this research is using descriptive analysis. The results of this study indicate that in the first cycle, the percentage of classical completeness of learning outcomes and the average level of activeness of students was 18% and 76%, respectively. Whereas in cycle II, the percentage of classical completeness of learning outcomes and the average level of activeness of students was 76% and 90%, respectively. This proves that, the application of discovery learning learning models can improve the results and learning activeness of class XII MIA-1 MAN 1 East Lombok, especially three dimensional material.